The role of alternative splicing of the adhesion molecule, CD44, in lymphoid malignancy. Issue 10 (October 1998) - Irving, J A; Cain, G; Howard, M; Angus, B; Taylor, P R; Cattan, A R
Abstract : AIM: To investigate the expression of CD44 isoforms containing variant exon 6 (v6) in a well characterised cohort of patients with non-Hodgkin's lymphoma (NHL) and chronic lymphocytic leukaemia (CLL), and to correlate this with phenotype and disease course. METHODS: Cryostat sections of OCT embedded diagnostic nodal material from NHL patients and cryopreserved mononuclear preparations from CLL patients were used as sources of RNA. After reverse transcription, PCR was carried out with amplimers positioned at either side of the variant exon insertion site to amplify all possible CD44 isoforms. Those isoforms containing v6 were identified after Southern blotting and hybridisation with a radiolabelled oligonucleotide. RESULTS: Of 32 NHL samples analysed, 16 did not express CD44 isoforms containing v6, six expressed an isoform containing exon v6 alone, and 10 expressed v6 long isoforms which contained exon v6 in addition to other variant exons. These data did not correlate with lymphoma classification, disease staging, or the presence or absence of extranodal disease. However, those patients expressing v6 long CD44 isoforms had a worse overall survival than those that did not. The plateau of the survival curves was 50% compared with 82%. No v6 long isoforms were detected in the 21 CLL samples investigated. CONCLUSIONS: The expression of v6 long CD44 isoforms is associated with aggressive disease in NHL, independent of grade, stage, or presence of extranodal disease.